2021
DOI: 10.1016/j.bbrep.2021.101091
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of peroxisome proliferator-activated receptor α attenuates apoptosis and promotes migration of vascular smooth muscle cells

Abstract: Peroxisome proliferator-activated receptor (PPAR) α is widely expressed in the vasculature and has pleiotropic and lipid-lowering independent effects, but its role in the growth and function of vascular smooth muscle cells (VSMCs) during vascular pathophysiology is still unclear. Herein, VSMC-specific PPARα-deficient mice ( Ppara ΔSMC ) were generated by Cre-LoxP site-specific recombinase technology and VSMCs were isolated from mice aorta. PPARα deficiency attenuated VSMC ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 81 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…[49,50] PPAR𝛼 is ubiquitously expressed, including in endothelial cells and VSMCs in the vasculature. [51,52] We may therefore speculate that the changes in PBMC gene expression observed in our study is reflecting gene expression changes in the liver and the vasculature.…”
Section: Discussionmentioning
confidence: 70%
“…[49,50] PPAR𝛼 is ubiquitously expressed, including in endothelial cells and VSMCs in the vasculature. [51,52] We may therefore speculate that the changes in PBMC gene expression observed in our study is reflecting gene expression changes in the liver and the vasculature.…”
Section: Discussionmentioning
confidence: 70%
“…It is worth exploring the mechanistic link between PPARα and the mitochondrial function in VSMCs on a more detailed molecular basis. In addition to its role in attenuating the mitochondrial ROS production and maintaining the mitochondrial membrane potential, our previous work has also demonstrated that a PPARα deficiency can attenuate VSMC apoptosis induced by Ang II and hydrogen peroxide, and increase the migration of Ang II-challenged VSMCs [ 22 ], thus indicating a profound and complex role for PPARα in maintaining VSMCs homeostasis. Although we detected a PPARα reduction in VSMCs accelerated Ang II-induced mitochondrial oxidative stress, we did not further explore the PPARα target genes in VSMCs to establish a direct mechanistic link between mitochondrial dysfunction and hypertensive vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Ppara fl/fl mice on a C57BL/6J background were generated as previously described [ 21 ]. Ppara fl/fl mice were crossed with SM22α-Cre to produce VSMC-specific Ppara -deficient mice ( Ppara ΔSMC ) [ 22 ]. Two-month-old Ppara ΔSMC and Ppara fl/fl male mice were infused with saline or Ang II at 490 ng/kg per minute with micro-osmotic pumps (Alzet, Model 1004, Cupertino, CA, USA) for 28 days as described [ 23 ].…”
Section: Methodsmentioning
confidence: 99%